Perbandingan Sensitivitas dan Spesifisitas antara Pengukuran Lingkar Lengan Atas, Lingkar Pinggang dan Lingkar Leher untuk Identifikasi Anak dengan Obesitas - Irawati, Cempaka; Nugroho, Hari Wahyu; Budiani, Dyah Ratna (Nexus Kedokteran Klinik, 2014)
Background: Childhood obesity is a global phenomenon. Oneoften childreninthe worldare over weight. Then in Indonesia, the prevalence of childhood obesityis relatively increasedyear to year. Screening forobese childrenneeds to be doneearly, given thatobesity inchildhoodis likely to leadtoadultobesitylater. Anthropometric measurements are easy and inexpensive way. Therefore, there was some studies using anthropometryas the tool for identify obesityin addition to body mass index(BMI), which is the gold standard. However, there is no studies have compared the validity of assorted anthropometricas a tool to identify obese children, so that there searcherintends to compare the sensitivity and specificity between mid-upper arm circumference (MUAC), waist circumference (WC), and neck circumference (NC) in identification obese children. Methods: This study is observational analytic cross sectional approach. A sample included 72 children who were aged 6 to 12 years from four elementary school in Surakarta. Sampling population was obesity and healthy children (controls) who selected by simple random sampling had been carried out previously by fixed disease samples. Then the child was measured height, weight, MUAC, WC, and NC. Height and weight will be converted into BMI to determine obesity or not. Data were analyzed with diagnostic tests are grouped in table 2x2. From diagnostic test, we can determine the sensitivity and specificity. Furthermore, data were analyzed by Chi Square test and analysis receiver operating characteristic curve (ROC) to determine accuracy. Results: Among 72 children, 51,4% are male. MUAC (â¥ percentile 90th), WC (â¥ percentile 90th) and NC (cut off point 27,0-31,5) are significantly correlated with BMI. The sensitivity of MUAC was 58,33% with specificity 100%. The sensitivity of waist circumference was 66,67% with specificity 97,22%. The sensitivity of the neck circumference was 80,56% with specificity 63,89%. Conclusions: MUA Cisthe best measuring tool to identification obesityin children because it hasthe highest specificity, that is 100%. Keywords: Mid-upper arm circumference, waist circumference, neck circumference, obesity, childrenÂ